ANALISIS PENGGUNAAN KARTU KATA BERGAMBAR BERBASIS CANVA DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Syakila Anatasya Putri, Alivia; Amalia, Sophie; Jannah, Roudhotul; Farhurohman, Oman (STKIP Subang, 2026)
This study examines the use of Canva-based picture word cards in improving early reading skills of elementary school students. The problem addressed in this research is the low level of students’ beginning reading ability, which is influenced by limited use of engaging learning media and teacher-centered instruction. The purpose of this study is to analyze early reading skills, identify learning problems, and evaluate the effectiveness of picture word cards designed using Canva. This research employs a Systematic Literature Review (SLR) method by collecting, selecting, and analyzing relevant studies published between 2020 and 2025. The data were analyzed using content analysis techniques to identify patterns, themes, and findings related to the use of visual learning media in early reading instruction. The results indicate that the use of picture word cards can significantly improve students’ ability to recognize letters, syllables, and simple words, as well as enhance reading fluency, motivation, and participation. Furthermore, integrating Canva in developing learning media contributes to more creative, interactive, and student-centered learning environments. Despite some challenges such as limited digital skills among teachers, this media proves to be an effective and innovative solution to enhance early reading skills in elementary education.